Collective Bargaining and Management Contract in Hospitality Industries: Issues in Contract for Industrial Feedings - Mark, John; Monday, Sholokwu Boniface (NIU Journal of Social Sciences, 2020)
This article examines the effect of collective bargaining on management contract in the hospitality industry. The data used for drawing inference was from reviewed literature. A qualitative and quantitative view of collective bargaining was taken from the dimensions of distributive bargaining, integrative bargaining, productivity bargaining and composite bargaining, whereas the management contract was seen from service and operations contract. The study adopted the stratified sampling technique in collecting its data. A total of 52 respondents were drawn from six (6) hotels in Port Harcourt. Spearman rank order correlation coefficient was the adopted statistical tool used in analyzing the collected data. The literature revealed that both the distributive and the productivity bargaining had more influence on the service contract, while the integrative and the composite bargaining had more influences on the operations contract as revealed by the statistical calculations. Therefore, the paper concluded that collective bargaining had influence on management contract. Keywords: collective bargaining, integrative bargaining, productivity bargaining, management contract, supply-service contract.